Loss Due to Death and its Association with Mental Disorders in Juvenile Detainees. (June 2015) - Harnisher, Julie Laken; Abram, Karen; Washburn, Jason; Stokes, Marquita; Azores‐Gococo, Nicole; Teplin, Linda
Abstract This study investigated the prevalence of loss due to death and its association with mental disorders in a random sample of 898 newly detained adolescents in Chicago, Illinois. Nearly 90% of youth experienced the loss of an important person; most had also experienced a "high‐risk" loss (e.g., loss due to violence, sudden loss). Minority youth were at particular risk. Youth with any loss or multiple losses were more likely to have mood disorders and ADHD/behavioral disorders, respectively, than youth who had no such losses. Interventions focusing on modifiable protective factors following loss may increase positive outcomes in this vulnerable population.